Local variations of air temperature at Delhi - AGARWAL, K. S. (MAUSAM, 1960)
In this paper the results of analysis of the monthly mean maximum and minimum air temperature recorded at three observatories situated at (a) Safdarjung Airport, (b) Lodi Road and (c) Palam Airport in the Delhi area during the years 1955-57 have been given and local variations of temperatures have been discussed.